Respuesta :
Inverses are easy for this problem. First we start with the equation. Then we change the f(x) to y to make this whole problem easier.
y=2x+1
Isolate the x and solve for x.
x=(y-1/2)
Switch x and y again.
y=(x-1/2)
Add function notation.
f^-1(x)=(x-1/2)
Done! And if you need to check if equations are inverses, add the original equation into the x variable of the inverse. The solution should be f^-1(x)=x. That means the inverse is right.
y=2x+1
Isolate the x and solve for x.
x=(y-1/2)
Switch x and y again.
y=(x-1/2)
Add function notation.
f^-1(x)=(x-1/2)
Done! And if you need to check if equations are inverses, add the original equation into the x variable of the inverse. The solution should be f^-1(x)=x. That means the inverse is right.
Answer:
[tex]f^{-1}(x)=\frac{x}{2}+\frac{1}{2}.[/tex]
Step-by-step explanation:
As we have a lineal function, there is a easy way to find the inverse [tex]f^{-1}(x)[/tex]:
First, switch the x and y, that is if we have
y = f(x) = 2x-1, then after the change we obtain
x = 2y-1.
Then, clear y:
[tex]x = 2y-1[/tex]
[tex]x+1 = 2y[/tex]
[tex]\frac{x+1}{2} = y[/tex]
[tex]\frac{x}{2}+\frac{1}{2} = y.[/tex]
Then, [tex]f^{-1}(x)=\frac{x}{2}+\frac{1}{2}[/tex] is the inverse of y=2x-1.
You can check it composing both functions, if you obtain x the inverse is correct.
[tex]f(f^{-1}(x))= 2(\frac{x}{2}+\frac{1}{2})-1[/tex]
[tex]f(f^{-1}(x)) = \frac{2x}{2}+\frac{2}{2}-1[/tex]
[tex]f(f^{-1}(x)) = x+1-1[/tex]
[tex]f(f^{-1}(x)) = x.[/tex]